Investigation into the Identification of Topics in Chat Messages - Loh, Stanley; Lichtnow, Daniel; Saldaña, Ramiro; Borges, Thyago; Primo, Tiago; Kickhöfel, Rodrigo Branco; Simões, Gabriel (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL), 2004)
This paper investigates the process of classification of textual messages in a web chat. This kind of text has special characteristics, like concision, orthographic mistakes, mainly by being written in a hurry and by naïve people. In this work, simple methods were evaluated to raise some specialties of the process.